The Pathogenesis of Primary Biliary Cholangitis: A Comprehensive Review - Lleo, Ana; Leung, Patrick S.C.; Hirschfield, Gideon M.; Gershwin, Eric M. (Seminars in Liver Disease, 2020)
Primary biliary cholangitis (PBC) is a chronic cholestatic liver disease characterized by autoimmune destruction of small to medium size intrahepatic bile ducts. The etiology of PBC remains unknown and pathogenesis features immune-mediated biliary injury, alongside the consequences of chronic cholestasis. PBC is strongly associated with the loss of immune tolerance against mitochondrial antigens and the subsequent presence of an articulated immunologic response that involves both humoral and cellular responses. Both environmental factors and genetic variants increase PBC susceptibility. Biliary epithelial cells have often been considered a passive target of the immune attack in PBC; however, cholangiocyte dedifferentiation, senescence, stress, and deoxyribonucleic acid damage have been recognized to play an active role in the pathogenesis of PBC. This review highlights and discusses the most relevant pathogenetic mechanisms in PBC, focusing on the key factors that lead to the onset of cholestasis and immune activation.
Keywords: primary biliary cholangitis; biliary epithelial cells; mitochondrial antibodies; apoptotic bodies